R&D tax incentives in industry: empirical study among small and medium electronics manufacturing enterprises - Nina Bockova (Institute of Economic Research (IER), 2015)
The paper deals with the topic of direct and indirect support for research and development and its use in small and medium-sized enterprises operating in the electronic industry. The Czech Republic is the geographic segment to be explored. A chapter on theoretical issues is followed by a description of the current situation in the Czech Republic and abroad and access to legal support for research and development in the business sector. Primary data collected from a survey are analysed in the analytical part. Some small and medium-sized enterprises of chosen group of manufacturing industry focus on research and development performed by they own means and they searched the possibility of financing the research from various sources. The initiative of these enterprises increase considerably their competitiveness in the global market and they realize the necessity of the innovation policy in the strategic management of the business, but still they do not make full use of all available supports in research and development from public sources and instruments of fiscal policy, which allows the legislation of the Czech Republic.
Keywords: E61; H29; D92; 330; small & medium-size enterprises; R&D tax deductible; own research and development; Czech Republic